Gugatan Class Action dalam Perspektif Hukum Positif di Indonesia - Mikako Naiya Putri; Tito Jeremia Sanggam Marisi Situmorang (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study aims to analyze the normative framework, consistency of application, and direction for strengthening class action lawsuit regulations from the perspective of positive law in Indonesia. The background of this study stems from the discrepancy between the growing need for collective dispute resolution and the limitations of procedural law regulations, which remain fragmented and lack integration. The method employed is normative legal research using a legislative, conceptual, and case-based approach, through an analysis of various regulations such as PERMA No. 1 of 2002, the Consumer Protection Act, and the Environmental Protection and Management Act, which were examined qualitatively using systematic and teleological interpretation. The research findings indicate that, normatively, class action regulations are in place; however, their implementation remains inconsistent due to unclear legal parameters and divergent judicial interpretations. Additionally, regulatory fragmentation was identified, which impacts the low effectiveness of collective legal protection. This study contributes recommendations for normative reconstruction through more comprehensive codification, strengthening of procedural mechanisms, and integration across legal regimes to enhance legal certainty and the effectiveness of law enforcement in the resolution of collective disputes.